Hospital mortality among COVID-19 patients – Experience of a multi-disciplinary tertiary care teaching hospital of Chhattisgarh in Central India - Tridip Dutta Baruah; Pankaj Kumar Kannauje; Rubik Ray; Nitin Borkar; Sunil Panigrahi; Deepak Kumar; Madhumallika Pathak; Debarati Biswas (Journal of Family Medicine and Primary Care, 2022)
Introduction: The mortality from coronavirus disease 2019 (COVID-19) infection and the severity of it vary among populations. There is a dearth of research on epidemiology and clinical outcomes in central Indian populations with COVID-19. Our aim was to provide an analysis of all hospitalized mortality among patients with COVID-19 infection in a tertiary care hospital of Chhattisgarh in central India. This analysis helped us to know the severity predictors for mortality and in future will help the authorities to formulate a plan to decrease the mortality in the epidemic or uncertain ongoing pandemic. Methodology: This was a retrospective observational study using the hospital-based record of multi-disciplinary teaching hospital in Chhattisgarh, India. All COVID-19 reverse-transcriptase polymerase chain reaction-positive patients who were declared dead or died during the course of treatment from April 1, 2020 to March 31, 2021 were included in the study. In-hospital mortality was the primary outcome of interest. In secondary analysis, age and gender distribution, co-morbidity, length of stay, and the cause of death were also investigated. Results: A total of 7495 patients with a confirmed diagnosis of COVID-19 were enrolled in the study, of whom 762 (10.16%) died in the hospital with COVID-19 as the primary cause of death. The majority of the patients were more than 60 years of age (45.7%). A total of 416 (54.4%) of the deceased patients were having co-morbidity with diabetes (13.4%), hypertension (16.4%), or both (24.4%). The majority of the patients who succumbed had a hospital stay of less than a week (≤7) (68.5%). More than half of the patients (58.3%) who expired had referred and reported to the hospital in the second or third week of illness. The respiratory system involvement was the dominant contributor of death with pneumonia (78.8%) being the most common cause, followed by acute respiratory distress syndrome (62.2%). 13.6% of expired patients had multiple system involvement, and 11.2% had sepsis as well. Conclusion: Mortality in COVID-19 patients was associated with advanced age, co-morbidities such as diabetes and hypertension, and delay in hospitalization. These are high-risk groups and should be vaccinated against COVID-19 on priority.